Personality structure assessment of people with opiate addiction and people with internet addiction disorder - Milinović Milica; Tepšič-Ostojić Vesna (Halo 194)
Introduction/Objective Problematic internet use is a psychophysical disorder that involves withdrawing from social interactions, a buildup of tolerance, affective disturbances and pathological social relationships. Neurobiological and pharmacological data suggest similarities between the pathophysiology of opiate addiction and pathological gambling. The objective of this research was to compare the sociodemographic characteristics of people with Internet Addiction Disorder, people who are addicted to opiates and the control group. Based on the Big Five model, psychological and psychopathological characteristics are then compared to determine their expression levels in all three groups. Methodology The research was carried out as a cross-sectional clinical study based on the methodological approach that included applying comparative methodology, using assessment scales and a psychological and psychiatric battery of tests for personality assessment. The sample included 300 subjects: 100 subjects with opiate addiction, 100 subjects showing symptoms of Internet Addiction Disorder, and 100 subjects of the control group. Results The results of this research indicate that personality traits such as empathy, extroversion, pleasantness, conscientiousness, openness and cooperation are expressed to a lesser extent in people with Internet Addiction Disorder and people addicted to opiates compared to the control group. Conclusion The obtained results serve to suggest that Internet Addiction Disorder should be included in the diagnostic category of behavioural addictions.